Research on the Fatigue Performance of TC6 Compressor Blade under the CCF Effect - Zhang Yakui; Guo Shuxiang (International Journal of Aerospace Engineering)
This paper studied the influence of high and low combined fatigue (CCF) on compressor blade fatigue performance. We investigated the coupling between low cycle fatigue (LCF) loading from centrifugal force with high cycle fatigue (HCF) loading from vibration and determined the blade disc vibration frequency using static analysis at maximum rotational speed. We designed and constructed a combined fatigue test rig, and CCF tests were performed on a TC6 compressor blade to analyze fatigue life characteristics. Results showed that CCF could significantly shorten blade life compared with pure LCF and that larger HCF caused more significant fatigue life reduction. Fatigue source characteristics and CCF fracture appearance were observed and analyzed using a scanning electron microscope (SEM).